Way to sustainable development sustainable society - Szekeresné Köteles Rita (Agrár- és vidékfejlesztési szemle, 2011)
Based on the results of a questionnaire survey sent to the LEADER LAGs in 2010 March, this study presents some social aspects of sustainability of rural areas. In this study I deal with some forms of participation as a basis and one of the main characteristic of social sustainability. Cooperation or willingness to cooperate, interest, ability to innovate, confidence, existence of key people, information flow, as well as commitment can be considered as forms of participation and a basis for sustainable society of rural areas. The results of the survey indicates that social participation as a tool for the so called social pillar of sustainability must be a subject for development in order to achieve sustainable development in general.